International security and gender - Detraz, Nicole (Cambridge, UK : Polity, 2012)
The author'explores the broad terrain of security studies through a gender lens ... By examining issues of militarization, peacekeeping, terrorism, human and environmental security, the book considers how the gender-security nexus pushes us to ask different questions and broaden our sphere of analysis. Including gender in our analysis of security challenges the primacy of traditional security concepts and shifts the focus to be more inclusive ...Our society often expects men and women to play different roles, and this is no less true in the realm of security. This book demonstrates that security debates exhibit gendered understanding of key concepts and, while these gendered assumptions may benefit specific people, they are often detrimental to others, particularly in the key realm of policymaking.'--par. 4 of back cover
Series statement from back cover.
Includes bibliographical references (p. 212-240) and index.
Keywords: Security, International -- Social aspects; National security -- Social aspects; Women and war; Feminism; Feminist theory